2015
DOI: 10.1073/pnas.1423967112
|View full text |Cite
|
Sign up to set email alerts
|

The EBF transcription factor Collier directly promotes Drosophila blood cell progenitor maintenance independently of the niche

Abstract: The maintenance of stem or progenitor cell fate relies on intrinsic factors as well as local cues from the cellular microenvironment and systemic signaling. In the lymph gland, an hematopoietic organ in Drosophila larva, a group of cells called the Posterior Signaling Centre (PSC), whose specification depends on the EBF transcription factor Collier (Col) and the HOX factor Antennapedia (Antp), has been proposed to form a niche required to maintain the pool of hematopoietic progenitors (prohemocytes). In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
149
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(163 citation statements)
references
References 46 publications
10
149
2
Order By: Relevance
“…It regulates head development (Crozatier et al, 1996, is important for embryonic muscle cell fate specification Dubois et al, 2007) and regulates hematopoietic progenitor cell fate (Pennetier et al, 2012;Benmimoun et al, 2015). KNOT is expressed in postmitotic neurons and controls class IV-specific dendritic arbor morphology in the Drosophila peripheral nervous system (Crozatier and Vincent, 2008;Hattori et al, 2013;Jinushi-Nakao et al, 2007).…”
Section: Maintenance Of Egfr Activity By Cap-d3mentioning
confidence: 99%
“…It regulates head development (Crozatier et al, 1996, is important for embryonic muscle cell fate specification Dubois et al, 2007) and regulates hematopoietic progenitor cell fate (Pennetier et al, 2012;Benmimoun et al, 2015). KNOT is expressed in postmitotic neurons and controls class IV-specific dendritic arbor morphology in the Drosophila peripheral nervous system (Crozatier and Vincent, 2008;Hattori et al, 2013;Jinushi-Nakao et al, 2007).…”
Section: Maintenance Of Egfr Activity By Cap-d3mentioning
confidence: 99%
“…It has been reported that PSC cells send out several molecular cues to regulate the differentiation state of the Lymph Gland, including Serrate (Ser), Hedgehog (Hh), Wingless (Wg, Wnt), Decapentaplegic (Dpp, BMP) and Pvf1 (PDGF/VEGF-related factor) [59, 66, 68, 74, 75]. A recent study has challenged the roles of the PSC and Hedgehog signaling in maintaining progenitor maintenance, although it did confirm PSC function in inducing lamellocyte differentiation upon parasitization [76]. Serrate expression and the consequent activation of Notch signaling are required for crystal cell production [59] and maintaining the expression of Collier, a transcription factor which is highly expressed in PSC cells and has roles in the Lymph Gland response to wasp infestation [67, 76].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has challenged the roles of the PSC and Hedgehog signaling in maintaining progenitor maintenance, although it did confirm PSC function in inducing lamellocyte differentiation upon parasitization [76]. Serrate expression and the consequent activation of Notch signaling are required for crystal cell production [59] and maintaining the expression of Collier, a transcription factor which is highly expressed in PSC cells and has roles in the Lymph Gland response to wasp infestation [67, 76]. Wingless signaling has a dual role in the Lymph Gland.…”
Section: Introductionmentioning
confidence: 99%
“…A centrally located medullary zone (MZ) contains prohemocytes with stem cell-like properties, whereas differentiating hemocytes are located in the peripheral cortical zone (CZ) (Evans et al, 2009;Jung et al, 2005). In addition, a small group of cells termed the posterior signaling center (PSC) controls differentiation and specification of hemocytes in the CZ (Benmimoun et al, 2015;Oyallon et al, 2016). Although much remains to be understood, the fly LG has developed into a powerful model for hematopoiesis and stem cell/progenitor regulation (Crozatier and Meister, 2007;Crozatier and Vincent, 2011;Letourneau et al, 2016;Martinez-Agosto et al, 2007;MorinPoulard et al, 2013;Shim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%